CRYOABLATION IN ATRIAL FIBRILLATION: RATIONALE OF THE NATIONAL PROSPECTIVE REGISTRY AND PRELIMINARY RESULTS - E. N. Mikhailov; T. A. Lyubimtseva; K. V. Davtyan; A. G. Topchian; E. S. Tarasyuk; D. V. Kryzhanovskiy; A. Ya. Kosonogov; I. Sh. Sagitov; D. N. Khomutinin; N. I. Grachev; A. Sh. Revishvili; E. A. Artyukhina; et al. (Российский кардиологический журнал, 2018)
Aim. Current registry is the continued national study on cryoablation in atrial fibrillation (AF). The aim of the project is assessment of safety and efficacy of cryoballoon ablation of pulmonary veins from AF treatment in real clinical practice prospective observation.Material and methods. The project has been developed for prospective inclusion of the data to guarded automatic informational system, on clinical data of patients, ablation parameters, repeat ablation and results of 12-month follow-up. To participate in the project in January of 2017, the representatives of 33 in-patient facilities were invited, that routinely perform the procedure.Results. Twenty five institutions confirmed their participation, and by December of 2017, the database was completed by specialists from 13 clinics: information on the ablation procedure and outcomes is included for 451 patient. The enrollment is ongoing with estimated end by January 2019; prospective follow-up to be completed by January 2020.Conclusion. Prospective registry of AF cryoablation is important for gathering of experience and common analysis of the procedures throughout the country. Detailed analysis will make it to reveal predictors of efficacy and methods for procedural risk decrease.